Reimagining Public Health in the Aftermath of a Pandemic - Brownson, Ross C.; Burke, Thomas A.; Colditz, Graham A.; Samet, Jonathan M. (American journal of public health (1971), 2020)
The coronavirus disease 2019 (COVID-19) pandemic is an unprecedented challenge for society, affecting those already subject to unacceptable health inequalities and resulting in vast economic impacts. The pandemic reminds everyone of the value and necessity of public health. In the context of an era that will be shaped by COVID-19, we outline the coming series of challenges and transitions in public health and the needed actions over the next 5 years to reinvent our public health systems. Multiple limitations in current US and global public health systems have been uncovered by the pandemic, including insufficient preparedness and surveillance capabilities complicated by long-standing and worsening health inequalities and the rapid spread of misinformation that needs to be countered. We foresee 3 phases for public health over the next 5 years: (1) reactive crisis management, (2) efforts to maintain initial gains, and (3) efforts to sustain and enhance progress. A reinvented public health system will depend highly on leadership and political will, rethinking how we categorize and address population-level risk, employing 21st-century data sciences, and applying new communication skills.